3D-printed, carbon-based, lossy photonic crystals: Is high electrical conductivity the must?. (January 2021) - Kuzhir, Polina; Paddubskaya, Alesia; Bychanok, Dzmitry; Liubimau, Aleksandr; Ortona, Alberto; Fierro, Vanessa; Celzard, Alain
Abstract: The electromagnetic response of 3D-printed periodic carbon structures was investigated numerically and experimentally in the microwave (26–37 GHz) and terahertz (0.2–1.2 THz) frequency ranges. The reflection, transmission and absorption spectra, as well as the effects of the concentration of electromagnetic waves, were analysed and discussed. High broadband absorption was observed for the 3D-printed cellular structures based on a moderately conductive (1–30 S m −1 ) skeleton, whereas perfect tuneable resonant absorption could be achieved by 3D meshes made of highly conductive (1200–2000 S m −1 ) glassy carbon. We show that laser stereolithography (SLA) or fused deposition modelling (FDM) 3D-printing technique should be preferred for getting pre-defined required electromagnetic performances depending on the intended application. Graphical abstract: Image 1